Od kaźni i tortur do uwięzionej socjalizacji. O genezie i rozwoju systemu profilaktyki i resocjalizacji - Ambrozik, Wiesław (Wydawnictwo Naukowe UAM, 2013)
This article reveals the origins and evolution of the prevention and social rehabilitation system and emphasises the juridical and criminological concepts of moral and legal improvement which have shaped the current theory and practice. Because the rehabilitation system follows the concepts that are diffi cult to implement in practice, it prejudges the effi ciency and effectiveness of the system.
From torment and torture to imprisoned socialization. The origins and evolution of the prevention and social rehabilitation system
Keywords: prevention and social rehabilitation system; juridical and criminological system; punishment in criminology and pedagogy